Epilepsy-Related Voltage-Gated Sodium Channelopathies: A Review - Menezes, Luis Felipe Santos; Sabiá Júnior, Elias Ferreira; Tibery, Diogo Vieira; Carneiro, Lilian dos Anjos; Schwartz, Elisabeth Ferroni (Frontiers in Pharmacology, 2020)
Epilepsy is a disease characterized by abnormal brain activity and a predisposition to generate epileptic seizures, leading to neurobiological, social, cognitive and psychological consequences for the patient. There are several known causes for epilepsy; one of them is the malfunction of ion channels, resulting from mutations. Voltage-gated sodium channels (Nav) play an essential role in the generation and propagation of action potential, and a failure in their activity caused by mutations can induce irregular neuronal activity. Therefore, several genetic variations in Nav channels have been described and associated with epilepsy. These mutations can affect channel kinetics, modifying the channel activation, inactivation, recovery from inactivation, and/or the current window. Among the Nav subtypes related to epilepsy. Nav1.1 is doubtless the most relevant, with more than 1.000 possible mutations described. The truncation and missense mutations are the most observed alterations. In addition, several studies have already related mutated Nav channels with the electrophysiological functioning of the channel, aiming to correlate with the epilepsy phenotype. The present review provides an overview of studies on epilepsy-associated mutated human Nav1.1, Nav1.2, Nav1.3, Nav1.6, and Nav1.7.